Attitudes toward mathematics and virtual teaching of students in the context of COVID-19: validation and reliability of instruments - Bazalar-Palacios, Janina (2024)
[Background]: There are few instruments to assess attitudes toward mathematics and virtual teaching; Likewise, there are methodological limitations to study this phenomenon in high school students. The present study aims to evaluate the psychometric properties of the instruments of attitudes toward mathematics and the perception of virtual teaching during COVID-19 in high school students in Peru. [Methods]: A total of 400 students participated. The research utilized exploratory and confirmatory factor analyses to evaluate the attitudes mathematics and the perception of virtual teaching instruments’ structure, and assessed reliability through Cronbach’s Alpha (α), Ordinal Alpha (ordinal α), and Omega (Ω) indicators. [Results]: Exploratory factor analysis showed that Model 2, with factor loadings above 0.40, was the most suitable for both instruments. This model demonstrated acceptable fit indices (CFI and TLI > 0.90; RMSEA and SRMR <0.08) and internal consistency (α, ordinal α, and Ω > 0.60). Furthermore, confirmatory factor analysis validated a five-dimensional structure for attitudes toward mathematics and a six-dimensional structure for perceptions of virtual teaching. [Conclusion]: Both instruments are valid and reliable for assessing these attitudes and perceptions within the context of virtual education during the COVID-19 pandemic. Strengthening mathematical skills through targeted research and interventions is essential to addressing pandemic-induced gaps.